Purchotius Græcus I: Vikentios Damodos' Concise ethics - Demetracopoulos, John A. (Verbum – Analecta Neolatina, 2010)
Most of the writings produced during the 18th century in one of the regions peripheral to the centers of philosophical, theological, and scientific development in Europe, namely, Greece, were but translations or adaptations of various works written in Latin, French, Italian, German, or English. Even some of the texts signed by their authors as produced by themselves are translations or adaptations, too. This is the case with most, if not all, of the philosophical (and theological) writings of Vikentios Damodos (1700–1754), a private teacher of Philosophy in Kefallenia (Ionian Islands, Greece), who had studied in Venice and Padova. His Concise Ethics, which forms part of his huge Concise Philosophy, is just a selective translation or adaptation (enriched only by few trivially didactic or confessional comments) of passages from the respective volume (Ethics) of Edmond Pourchot's (1651–1734) Institutiones philosophicæ as well as from the homonymous part (Compendium Ethicæ) of Vol. V (Exercitationes Scholasticæ) of the same textbook. Damodos, by plagiarizing Pourchot, transmitted to Greece a potentially progressive eclectic philo-Cartesianist Christian philosophy taught at the time in France, Italy, Ukrainia and elsewhere.